2010
DOI: 10.5171/2010.862128
|View full text |Cite
|
Sign up to set email alerts
|

Instructors' Acceptance of Learning Management Systems: A Theoretical Framework

Abstract: In the knowledge age, the use of the information technology (IT) tools including learning management systems (LMS) has became an imperative. The adoption rate of LMS in academic and training institutions is very promising worldwide. Learning Management system includes several tools that provide academic and training institutions efficient and effective means to support distance education and supplement their traditional way of teaching. LMS also provide academic insinuations mechanisms and tools to store, mana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
90
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(96 citation statements)
references
References 31 publications
2
90
0
4
Order By: Relevance
“…7 The TAM provided a framework of the critical factors that influence users' perceived ease of use and perceived usefulness of learning management systems and consequently can be used to predict actual use. 7 Both these constructs are critical in facilitating adoption of new technology, and the underpinning factors of system design, technical issues, familiarity with technology, and time were the most frequent limiting factors identified in other studies. 8 The questionnaire consisted of 35 questions on demographics and questions structured to measure the TAM framework.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…7 The TAM provided a framework of the critical factors that influence users' perceived ease of use and perceived usefulness of learning management systems and consequently can be used to predict actual use. 7 Both these constructs are critical in facilitating adoption of new technology, and the underpinning factors of system design, technical issues, familiarity with technology, and time were the most frequent limiting factors identified in other studies. 8 The questionnaire consisted of 35 questions on demographics and questions structured to measure the TAM framework.…”
Section: Methodsmentioning
confidence: 99%
“…6 To achieve flexibility and greater utility of learning management systems, the evaluation of students' experiences in using learning management systems is essential to address the pedagogic needs of both the students and teaching staff. 1 Using a structured theory, such as the Technology Acceptance Model (TAM), 7 which models how students may accept and use a technology based on two factors (perceived ease of use and perceived usefulness), these systems could be regularly evaluated for ease of use and usefulness in providing students with feedback and to establish whether the systems can support material in different formats. 6 A systematic review found that perception of benefits or usefulness of the system was the most common facilitating factor in uptake.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…www.ijacsa.thesai.org TAM is one of the most effective research models to determine factor acceptance of information systems/technology [43]. TAM is also commonly used to measure user behaviour and to identify the factors influencing users" acceptance of new technologies [38], [44]- [46].…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…The rationale behind adoption and usage of LMS can be best understood by its functionalities simply because it has become a complimentary medium for course-content delivery in both blended learning environments and completely online learning environments. As indicated in recent studies, LMS allows' students to access course information anywhere and anytime, according to their preferences (Asiri, Mahmud, Abu Bakar, & Mohd Ayub, 2012;Al-Busaidi & Al-Shihi, 2010). LMS also provides a medium for assignment marking, handout note making, and uploading and downloading (Asiri et al, 2012;Govindasamy, 2001).…”
Section: Introductionmentioning
confidence: 99%